An Unusual Cause of Generalized Swelling - Shahrin, Sabrina; Islam, Md Aminul; Khan, Md Ehsan Uddin; Ahmed, Parvez Iftekhar; Islam, Md Nazrul; Chowdhury, Md Nizamuddin (Journal of Dhaka Medical College, 2018)
Amyloidosis and multiple myeloma are included in the same spectrum of clonal plasma cell disorder. Amyloidosis can present with localized deposits or manifest as systemic disease involving multiple organs such as kidney, heart, intestine. Free Ig subunits ,mostly light chains secreted by a single clone of B cells, are the cause of the most frequent and severe amyloidosis affecting the kidney. The incidence of AL amyloidosis is nine per 1 million populations per year. Amyloid deposists are found in approximately 10% of all patients with myeloma and in 20% of those with pure light chain myeloma[1].Here we are reporting a case who initially presented with generalized swelling and subsequently found to have AL amyloidosis involving multiple organs due to multiple myeloma. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 173-177